2018
DOI: 10.1002/maco.201709972
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing maleic anhydride microcapsules size for use in self‐healing epoxy‐based coatings for corrosion protection of aluminum alloy

Abstract: Due to the significance of self‐healing coatings in recent years, there has been increasing desire to optimize process parameters for effective control of functions of the coatings for durable application. Among various approaches for achieving desired optimized properties, the use of central composite design (CCD) of the response surface methodology (RSM) remains an effective and reliable technique. Thus, the objective of this study was to develop an appropriate model for optimization of size of microcapsule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As a disadvantage, the protection offered by organic layers is expensive, requiring constant replacement of the surfaces by painting; therefore, better alternatives are needed [1]. The type of organic compound used, the compactness and adhesion of the deposited layer dictate the quality of the protective layer and, as a result, its anti-corrosion protection [2][3][4]. Most organic coating systems include polymers (epoxies, acrylics, polyurethanes, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a disadvantage, the protection offered by organic layers is expensive, requiring constant replacement of the surfaces by painting; therefore, better alternatives are needed [1]. The type of organic compound used, the compactness and adhesion of the deposited layer dictate the quality of the protective layer and, as a result, its anti-corrosion protection [2][3][4]. Most organic coating systems include polymers (epoxies, acrylics, polyurethanes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of intelligent coatings capable of acting over time (self-healing and corrosion resistance) has been studied. Microcapsules using the double emulsion technique with similar action have been prepared [3,4]. The majority of intelligent coatings offer limited protection (the adherence of the newly formed film is crucial).…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that the additive of organotin is extremely toxic, which was forbidden in the EU in 2003 and globally in 2008 [8]. In recent years, the coatings based on organics [9,10] have been developed as alternatives, such as the epoxy coatings [11][12][13]. However, 90% epoxy coatings were achieved using diglycidyl ether of bisphenol A, deriving from bisphenol A. Bisphenol A has been proven to be harmful to the endocrine system and may cause feminization [14].…”
Section: Introductionmentioning
confidence: 99%
“…Kok-Hui Goh evaluates the effects of dosage, pH and contact time on high-dose phosphate inhibition for copper corrosion control and their interactive effects by RSM (Goh et al, 2008). Njoku uses RSM to optimize maleic anhydride microcapsules size for corrosion protection of aluminum alloy (Njoku1 et al, 2018).…”
Section: Introductionmentioning
confidence: 99%